Analysis of chaotic mixing in plugs moving in meandering microchannels - Che, Zhizhao (2012)
Droplets moving in meandering microchannels can serve as a passive and robust strategy to produce chaotic mixing of species in droplet-based microfluidics. In this paper, a simplified theoretical model is proposed for plug-shaped droplets moving in meandering microchannels at Stokes flow. With this model to provide the velocity field, particle tracking, which requires a large computation time, is performed directly and easily without interpolation. With this convenience, a broad survey of the parameter space is carried out to investigate chaotic mixing in plugs, including the channel curvature, the Peclet number, the viscosity ratio, and the plug length. The results show that in order to achieve rapid mixing in plugs in meandering microchannels, a large curvature, a small Peclet number, a moderate viscosity ratio, and a moderate plug length are preferred.